Sub-Acute Intestinal Obstruction – A Rare Complication in a patient with Autosomal Dominant Polycystic Kidney Disease: A Case Report - Naseer, Nazish; Yaqub, Sonia (Pakistan Journal of Kidney Diseases, 2021)
associated with vomiting and constipation. On examination he was an obese, ill looking male with a distended abdomen and bilateral palpable flank masses. Gut sounds were sluggish. Small and large bowel loops were found to be dilated on abdominal x-ray. Computed tomography scan of the abdomen showed grossly enlarged kidneys occupying almost whole of the abdomen pushing small bowel loops anteriorly. Based on clinical and radiological findings a diagnosis of sub-acute intestinal obstruction was made. Patient was managed conservatively (i.e. with NG tube and rectal decompression). This case highlights intestinal obstruction as a rare complication of ADPKD.